2017
DOI: 10.1007/s13205-017-1055-4
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of a novel tannase (tan B LP ) in endophytic Streptomyces sp. AL1L from the leaf of Ailanthus excelsa Roxb

Abstract: The tannase production ability by endophytic actinobacteria and the genetic identity of responsible tannase gene were determined. The studied strains were isolated from surface-sterilized leaf discs of Roxb. Four strains were found to hydrolyze tannic acid on solid media containing 0.4% tannic acid. The strain AL1L was found as indicating production of tannase with diverse of substrate affinity. The tannase production from the potential strain AL1L was performed in liquid tannic acid broth (0.4%, w/v). The str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Plants and their endophytes are co-evolutionary partners and thus share valuable genes. They are factories of novel bioactive compounds with unique biotechnological importance in the control, prevention and amelioration of fatal diseases by producing antimicrobial, antioxidative, and anticancer compound sand industrially valuable enzymes [ 4 , 5 , 6 , 7 , 8 ]. Hydrocarbon derivatives from endophytic sources with bio-fuel potency are popularly known as myco-diesel and provide a glimpse into the ecology of fungus–plant and environmental relationship [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plants and their endophytes are co-evolutionary partners and thus share valuable genes. They are factories of novel bioactive compounds with unique biotechnological importance in the control, prevention and amelioration of fatal diseases by producing antimicrobial, antioxidative, and anticancer compound sand industrially valuable enzymes [ 4 , 5 , 6 , 7 , 8 ]. Hydrocarbon derivatives from endophytic sources with bio-fuel potency are popularly known as myco-diesel and provide a glimpse into the ecology of fungus–plant and environmental relationship [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Streptomyces sp. from leaf disks of Ailanthus excelsa Roxb showed 6.96 U/mL of activity at 30 °C, 48 h, 150 rpm …”
Section: Results and Discussionmentioning
confidence: 99%
“…from leaf disks of Ailanthus excelsa Roxb showed 6.96 U/mL of activity at 30 °C, 48 h, 150 rpm. 25 Bacillus licheniformis exhibited 0.356 U/mL tannase activity at 40 °C, pH 5.0, 21 h, 200 rpm. 26 Pseudomonas aeroginosa from Jamun and keekar leaves showed 13.65 U/mL at 37 °C, pH 7.0, 24 h, 200 rpm.…”
Section: 3mentioning
confidence: 97%
“…DNA was extracted by the CTAB method ( Wilson, 1987 ). Total genomic DNA of ten bacterial strains was subjected to PCR using 16S rDNA primers (universal) 27F (5′ AGAGTTTGATCMTGGCTCAG 3′), 1492R (5′ ACCTTGTTACGACTT 3′) ( Roy et al, 2018 ), and previously reported PCR conditions were applied. 55 °C was used as annealing temperature for 16S rRNA universal Primers amplification and 1500 bp PCR Product was obtained as described by ( Mushtaq et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%